Inter and intraspecific competition between the fox species Alopex lagopus and Vulpes vulpes: an evaluation trial under penned conditions - Korhonen, Hannu T.; Alasuutari, Sakari; Mäkinen, Auli; Niemelä, Paavo (Springer-Verlag, 1997)
V ok TUR